USING STRUCTURED DIALOGUES TO PRACTICE CONVERSATION PATTERNS - Teshaboyeva Nafisa Zubaydulla qizi Scientific advisor: Jizzakh branch of the National university of Uzbekistan named after Mirzo Ulug’bek. The faculty of psychology, the department of Foreign languages; Philology and teaching languages: English Mardaqulov (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
Structured dialogues are a widely used method in language teaching, especially for developing communicative competence in speaking. By engaging learners in patterned, meaningful, and context-rich conversations, structured dialogues help reinforce grammar, vocabulary, and functional expressions in real-life scenarios. This article explores the theoretical foundations, benefits, and effective techniques of using structured dialogues in language classrooms to enhance students' speaking abilities.